التدرج في تطبيق الشريعة الإسلامية في ولاية آتشيه بإندونيسيا في ضوء مقاصد الشريعة الإسلامية - عارفين، عبد الغفور (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The aim of this research is to construct a general perception of the project of gradual application of Islamic law in the state of Aceh, Indonesia, in the light of the purposes of Islamic law. The researcher followed the inductive method in tracking and collecting scientific studies on the application of Islamic law in the state of Aceh and its stages and challenges, as well as the view of the purposes of Shari'ah in this application, the analytical approach to explain information about the gradual application of Islamic law and analysis of a proposed statement of the appropriate comprehensive stages in the light of the purposes of Shari'ah. The researcher exposed the definition of the hierarchy and its sections, its importance, its legitimacy, its means and its controls, with the statement of the reality of the application of Islamic law in the state of Aceh problems and challenges. He then added the importance of the purposes of Islamic Shari'ah in the formulation of the draft phases of the gradation in the application of Shari'ah with the presentation stages of the proposed gradation in the application of Islamic law in Aceh in light of the purposes of gradation. The researcher concluded this study by mentioning the most important findings with some recommendations. The results of the study are summarized in two important points: First, the model of the gradual application of the comprehensive Islamic law in the state of Aceh is considered to be one of the necessary interests related to the preservation of religion. If the religion is supported, all the necessary interests of the slave are fulfilled by self-preservation, mind, birth, money, and blessings and happiness in this world and hereafter. Secondly, the theory of Islamic political preparation and legal law is one of the most important means of reforming the state and religion in all areas of social, economic, educational, religious, judicial and cultural life on the basis of Islamic principles in this age. The success or failure of this project depends on the management of the ruler and the heads of government administration.